The Evolutionary Dynamics of a Novel Miniature Transposable Element in the Wheat Genome - Keidar-Friedman, Danielle; Bariah, Inbar; Domb, Katherine; Kashkush, Khalil (Frontiers in Plant Science, 2020)
The discovery of Mariam, a wheat-unique miniature transposable element family, was reported in our previous study. We have also shown the possible impact of Mariam insertions on the expression of wheat genes. However, the evolutionary dynamics of Mariam was not studied in detail. In this study, we have assessed the insertion sites of Mariam family in different wheat species. In-silico analysis of Mariam insertions has allowed the discovery of two different sequence versions of Mariam, and that Mariam might have been recently active in wild emmer wheat genome (T. turgidum ssp diccocoides). In addition, the analysis of Mariam insertional polymorphism has facilitated the discovery of large genomic rearrangement events, such as deletions and introgressions in the wheat genome. The dynamics of Mariam family sheds light on the evolution of wheat.